Estimates of Lp Modulus of Continuity of Generalized Bounded Variation Classes. (4th May 2014) - Wang, Heping; Wu, Zhaoyang
Abstract : Some sharp estimates of theL p 1 ≤ p < ∞ modulus of continuity of classes ofΛ φ -bounded variation are obtained. As direct applications, we obtain estimates of order of Fourier coefficients of functions ofΛ φ -bounded variation, and we also characterize some sufficient and necessary conditions for the embedding relationsH p ω ⊂ Λ φ B V . Our results include the corresponding known results of the classΛ B V as a special case.